Using Geocaching to Promote Active Aging: Qualitative Study - Fornasini, Silvia; Dianti, Marco; Bacchiega, Alessandro; Forti, Stefano; Conforti, Diego (JMIR Publications, 2020)
BackgroundOver the past few years, the development of technologies supporting active aging has been increasing. Among the activities that promote physical exercise by using technologies is geocaching-a treasure hunt of sorts in which participants use a receiver GPS to hide or find real or virtual objects. Although this activity is particularly suited to the promotion of healthy lifestyles in older people, geocaching remains to be unexplored in this area. ObjectiveThis study aimed to investigate the effectiveness of activities combining geocaching and self-tracking technologies to promote active aging, evaluate the usability of technologies, and explore the ways in which technologies have been integrated in the organizational context under examination to determine the user experience of participants. MethodsA group of individuals aged 65 years and older (N=14) attending a senior center managed by a social cooperative was involved in the study. Some of them created the geocaching contents, and others, split into 2 teams, participated in the game. Each participant was given a pedometer bracelet and the geocaching app. The steps taken by individual participants along with the number of caches found by each group translated into team scores. ResultsThe main results of the study were as follows: (1) activities in favor of active aging that involve the use of new technologies can foster the participation of elderly people; in particular, adding gamification to self-tracking can be a valid strategy to promote physical exercise among the elderly; (2) for this to happen, involvement of older people firsthand is crucial, and there must be a focus on their active involvement and empowerment in every phase of the project; and (3) the mediation of conflicts and competition that arise from the gamification could only take place because of the strong support of the organization in the form of social workers. ConclusionsThe results show that promoting active aging through technologies requires more effort than simply using these tools; it requires a wider process that involves an articulated organizational network with heterogeneous actors, technologies, and relations.